DOP062 The anti-MAdCAM antibody SHP647 in Crohn's disease: Endoscopic effects of induction therapy. (16th January 2018) - D′Haens, G R; Gorelick, K; Wang, Y; Cataldi, F; Sandborn, W J
Abstract: Background: Despite available treatments, patients with Crohn's disease (CD) often experience symptoms and complications of uncontrolled intestinal inflammation. SHP647 is a fully human IgG2қ anti-MAdCAM monoclonal antibody being developed for the treatment of patients with CD and ulcerative colitis. During the double-blind, randomised, controlled, phase 2 trial, OPERA I (NCT01276509), patients with CD were randomly assigned to receive placebo or SHP647. The aim of this post-hoc analysis of OPERA I was to examine changes in Simple Endoscopic Scores for CD (SES-CD) in patients who received placebo vs. SHP647. Methods: OPERA I was a multicentre clinical trial that included participants with moderate to severe CD, and ulcerations on colonoscopy performed at baseline as scored by SES-CD. Patients received SHP647 (22.5 mg, 75 mg, 225 mg s.c.) or placebo at baseline, week 4 and week 8, with optional colonoscopy at week 10 and Clinical Disease Activity Index (CDAI) scores determined at weeks 8, 10 and 12. This post-hoc analysis included patients who underwent endoscopy at baseline and week 10 with determination of SES-CD. SES-CD was determined by the investigator at both time points. Results: In total, 262 patients were enrolled and entered the treatment period; 15 (placebo: n = 4; SHP647 22.5 mg: n = 4; 75 mg: n = 4; 225 mg: n = 3) had endoscopy with SES-CD at both baseline and week 10. Mean (SD) SES-CD and CDAI-70 responses are shown in Table 1. Mean total SES-CD ulcerated surface scores (one of four SES-CD variables) across five segments (ileum, right colon, transverse colon, left colon and rectum) tended to decrease (improve) from baseline to week 10 (Table 2). Conclusions: In this post-hoc analysis of OPERA I data, there was a trend showing an improvement in endoscopic disease severity with SHP647 at the 22.5 mg dose. After administration of three doses, 22.5 mg SHP647 appeared to differentiate from placebo, 75 mg and 225 mg SHP647 in terms of SES-CD, with all patients experiencing at least a 25% decrease in score and these patients experiencing the greatest decrease in total ulcerated surface score. There was no consistent correlation between clinical and endoscopic improvement. Additional studies are needed to fully examine these findings.